Epigraphic and Archaeological Evidence Contributing to Identifying the Location and Character of Timacum Maius - Petrović, Vladimir P.; Filipović, Vojislav (Balcanica - Annual of the Institute for Balkan Studies, 2013)
Systematic archaeological excavation in the area of the village of Niševac near Svrljig, southeast Serbia, of a Roman settlement site, possibly Timacum Maius station on the main Roman road Lissus–Naissus–Ratiaria connecting the Adriatic and the Danube, has been going on for five years. Epigraphic and etymological analysis of an inscription dedicated to Hera Sonketene (dat. Ἥρᾳ Σονκητηνῇ) provides evidence for the possible balneological character of the entire area of Timacum Maius, which was geomorphologically similar to and connected by a road network with the Thracian region of Denteletika centred on Pautalia, where the dedicant, Tiberius Claudius Theopompus served as strategos. The archaeological evidence complements the conclusions suggested by the epigraphic material. The recently discovered second-century Roman structure furnished with a hypocaust system using perforated circular-sectioned pebble-filled ceramic tubuli for heating the floors and outer walls of the building may have served a balneal purpose. A sizeable Roman bathhouse, with remains of two pools and two rooms with a hypocaust and ceramic tubuli, has also been partially explored. In the broader area of Svrljig Valley (near the village of Prekonoga), a luxurious Roman villa with a marble hexagon, numerous rooms and a bath, recently subjected to a rescue excavation, has been completely cleared and recorded. The first geophysical survey on the Timacum Maius site has also been undertaken.